Respuesta :
Answer:
x=3
Step-by-step explanation:
How to solve your question
Your question is 1/2(4x-2)=6x-3
Solve
1.Combine multiplied terms into a single fraction
1/2(4x-2)=6x-13
1(4x-2) divided by 2 =6x-13
2.Multiply by 1
3 Subtract 6x from both sides of the equation
4.Simplify
5.Multiply all terms by the same value to eliminate fraction denominators
6.simplify
7.Add 2 to both side of equation
8.Simplify
9.Divide both sides of the equation by the same term
10.Simplify
Step-by-step explanation:
Combine multiplied terms into a single fraction
1/2 (4x-2) / 2 = 6x - 13
1 (4x -2) /2 = 6x -13
Multiply by 1
1 (4x - 2) / 2 = 6x - 2
4x - 2 / 2 = 6x-13
Subtract 6x from both sides of the equation
4x - 2 / 2 = 6x - 3
4x - 2 /2 - 6x =6x -13 -6x
Simplify
Combine like terms
4x -2 /2 -6x = -13
Multiply all terms by the same value to eliminate fraction denominators
4x -2 /2 -6x = -13
2 (4x-2 /2 -6x) =2(-13)
Simplify
Distribute
Cancel multiplied terms that are in the denominator
Combine like terms
Multiply the numbers
-8x -2 = -26
Add 2 to both sides of the equation
-8x -2= -26
-8x -2+2 = -26+2
Simplify
Add the numbers
Add the numbers
-8x = -24
Divide both sides of the equation by the same term
-8x = -24
-8x / -8 = -24 / -8
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=3
Solution
=3